2006
DOI: 10.4049/jimmunol.176.10.5943
|View full text |Cite
|
Sign up to set email alerts
|

Class I and III Phosphatidylinositol 3′-Kinase Play Distinct Roles in TLR Signaling Pathway

Abstract: PI3K involvement has been implicated in the TLR signal pathway. However, the precise roles of the different classes of PI3K in the pathway remain elusive. In this study, we have explored the functions of class I and class III PI3K in the TLR signal pathway using specific kinase mutants and PI3K lipid products. Our results reveal that class III PI3K specifically regulates CpG oligodeoxynucleotide (ODN)-induced cytokine and NO production as well as NF-κB activation, whereas class I PI3K regulates both CpG ODN- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 41 publications
(51 reference statements)
4
69
0
Order By: Relevance
“…PI3K and TLR signaling share several downstream signaling components (22,23,48), however, the role of PI3K in TLR4 signaling, such as LPS is controversial. Several papers (49,50) show that inhibition of PI3K leads to an increase in LPS-induced proinflammatory cytokines such TNF-␣ and tissue factor in monocytes and blood, suggesting that PI3K could be an endogenous inhibitor of LPS-induced cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K and TLR signaling share several downstream signaling components (22,23,48), however, the role of PI3K in TLR4 signaling, such as LPS is controversial. Several papers (49,50) show that inhibition of PI3K leads to an increase in LPS-induced proinflammatory cytokines such TNF-␣ and tissue factor in monocytes and blood, suggesting that PI3K could be an endogenous inhibitor of LPS-induced cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K and its downstream AKT have been shown to play an important role in promoting cell survival (10,30). CpG DNA/ODN can activate PI3K to regulate a variety of cellular responses (31,32). AKT has been shown to inhibit cell apoptosis in Rat1a fibroblasts in proportion to its kinase activity (33), and it has been reported that CpG DNA inhibits DC (2) and macrophage (34) apoptosis in a PI3K dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Results of densitometric analysis of the western blot data are expressed as mean values ± SD, where n = 3; *P < 0.01 vs control. by TLR downstream signaling [18]), ERK (known to stimulate NOS activation in macrophages [19]) and PKCd (found to play a role in Nox assembly in zymosanactivated human monocytes [20]) in R848-induced TLR7/8 signaling were investigated. Cells were pretreated with 30 µM Ly294002 (PI3-K inhibitor), 10 µM PD098059 (ERK inhibitor) and 20 µM rottlerin (PKCd inhibitor), followed by 4 h of stimulation with 0.1 µg/ml R848.…”
Section: Tlr7/8 Trigger Hif-1a Accumulation Via Redox-and Rns-dependementioning
confidence: 99%